TAXATION OF CRYPTOCURRENCIES IN THE DIGITAL ECONOMY: COMPARATIVE ANALYSIS AND POLICY RECOMMENDATIONS FOR UZBEKISTAN - Khujakulov I. B.; Rejabbayev. S. (Innovate Conferences, 2025)
This article provides a detailed examination of cryptocurrencies as an integral part of the modern digital economy, their role in the financial system, and the challenges associated with their taxation. It highlights that, unlike traditional currencies, cryptocurrencies are decentralized and anonymous, which significantly complicates their monitoring and regulation by tax authorities. The article includes a comparative analysis of the taxation practices of cryptocurrencies in countries such as the United States, Germany, Japan, Russia, and Uzbekistan. The author emphasizes that the legal status and classification of cryptocurrencies vary from country to country, making it difficult to establish a unified international tax policy in this area. Special attention is given to the regulatory framework governing the circulation of crypto assets in Uzbekistan, particularly the regulations adopted in 2022 and their impact on taxation practices. The author evaluates the effectiveness of current mechanisms for recording, declaring, and taxing income derived from cryptocurrencies and offers recommendations for their improvement. These include introducing dedicated tax reporting forms for digital assets, utilizing international information exchange systems, and implementing blockchain-based monitoring technologies for tax control. Overall, the article addresses a highly relevant topic by shedding light on contemporary issues of taxation in the context of the digital economy. It combines theoretical insights with practical suggestions, making it a valuable contribution to the development of an effective tax policy regarding cryptocurrencies.
Keywords: Cryptocurrency, digital assets, taxation, tax policy, Uzbekistan, blockchain, decentralized finance, fiscal regulation, international comparison